2022
DOI: 10.3390/foods11131943
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Modified Atmosphere Packaging with Different Gas Ratios on the Quality Changes of Golden Pompano (Trachinotus ovatus) Fillets during Superchilling Storage

Abstract: The quality changes of golden pompano fillets in air packaging (AP) and modified atmosphere packaging (MAP) with 30% CO2/70% N2, 50% CO2/50% N2, and 70% CO2/30% N2 were evaluated under superchilling (−3 °C). The results showed that the whiteness of fillets decreased during storage. The rate of pH increase of MAP was significantly slower than in AP groups, in which MAP with 70% CO2/30% N2 effectively suppressed the PH. Interestingly, the hardness decreased on day five following the treatments, followed by a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 41 publications
3
15
0
Order By: Relevance
“…The free radical species in ROS can induce and accelerate the lipid radical chain reaction, which leads to the increase in the TBARS value in meat [ 43 ]. In addition, fish meat is high in fat and rich in nutrients and is susceptible to microbial contamination, which leads to increased lipid oxidation in fish meat [ 7 ]. Kim et al [ 44 ] treated bacon with plasma and found the degree of lipid oxidation of the treated group was higher than that of the control group during storage.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The free radical species in ROS can induce and accelerate the lipid radical chain reaction, which leads to the increase in the TBARS value in meat [ 43 ]. In addition, fish meat is high in fat and rich in nutrients and is susceptible to microbial contamination, which leads to increased lipid oxidation in fish meat [ 7 ]. Kim et al [ 44 ] treated bacon with plasma and found the degree of lipid oxidation of the treated group was higher than that of the control group during storage.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the fish is sold as fresh, frozen, or refrigerated, all of which have a short shelf life, which reduces the economic value of golden pompano products [ 6 ]. The fresh-keeping technologies for T. ovatus are mainly freezing, modified atmosphere packaging (MAP) [ 7 ], and film coating [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 E showed the weight loss of Pacific white shrimp treated with essential oils during storage. The weight loss is mainly related with the drip loss of muscle, due to the decomposition, denaturation, or oxidation of proteins [ 38 , 39 ]. The changes of weight loss were indeed positively correlated with changes of bacterial growth, TCA-soluble peptide, and negatively correlated with protein contents displayed as following in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Modified atmosphere packaging (MAP) is an effective strategy for food preservation that inhibits microbial growth, decreases lipid oxidation, and protein degradation (5,6). Previous studies have shown that MAP improves the quality of fish and fishery products by inhibiting bacterial growth (7,8).…”
Section: Introductionmentioning
confidence: 99%